Purveyors of fine halos: re-assessing globular cluster contributions to the Milky Way halo buildup with SDSS-IV - Koch-Hansen, Andreas; Grebel, Eva K.; Martell, Sarah L. (Astronomy and astrophysics, 2019)
There is ample evidence in the Milky Way for globular cluster (GC) disruption. It may therefore be expected that part of the Galactic halo field star population may also once have formed in GCs. We seek to quantify the fraction of halo stars donated by GCs by searching for stars that bear the unique chemical fingerprints typical for a subset of GC stars often dubbed “second-generation stars”. These are stars showing light-element abundance anomalies such as a pronounced CN-band strength accompanied by weak CH-bands. Based on this indicator, past studies have placed the fraction of halo stars with a GC origin between a few to up to 50%. Using low-resolution spectra from the most recent data release (DR14) of the latest extension of the Sloan Digital Sky Survey (SDSS-IV), we were able to identify 118 metal-poor (−1.8 ≤ [Fe/H] ≤ −1.3) CN-strong stars in a sample of 4470 halo giant stars out to ∼50 kpc. This increases the number of known halo stars with GC-like light-element abundances by a factor of two and results in an observed fraction of these stars of 2.6 ± 0.2%. Using an updated formalism to account for the fraction of stars lost early on in the GC evolution, we thus estimate the fraction of the Galactic halo that stems from disrupted clusters to be very low, at 11 ± 1%. This number would represent the case that stars lost from GCs were entirely from the first generation and is thus merely an upper limit. Our conclusions are sensitive to our assumptions of the mass lost early on from the first generation formed in the GCs, the ratio of first-to-second generation stars, and other GC parameters. We carefully tested the influence of varying these parameters on the final result and find that under realistic scenarios, this fraction depends on the main assumptions at less than 10 percentage points. We further recover a flat trend in this fraction with Galactocentric radius, with a marginal indication of a rise beyond 30 kpc that could reflect the ex situ origin of the outer halo as is also seen in other stellar tracers.